Journal Review: Developments in TiSi2 Material Synthesis and Application Potential in Defence Industry Sector - Sinurat, Michael Tulus Samuel; Ansori, Ansori; Aritonang, Sovian; Putranto, Andy Marjono (CV. Rayyan Dwi Bharata, 2025)
Titanium disilicide (TiSi2) is a promising intermetallic material due to its unique properties, such as high temperature oxidation and corrosion resistance, good thermal and electrical conductivity, and low density. In this review article, various aspects of TiSi2 are discussed, including the properties and characteristics of the material, synthesis methods, applications, and development opportunities. The method used in writing this article is the Systematic Literature Review (SLR) by searching, collecting, and evaluating several sources related to the research object. Recent development in TiSi2 applications include semiconductors (Salicide technology which has lower resistivity), longer-lasting lithium-ion battery anodes, high temperature resistant coatings and components, hydrogen generators and defence system components. With the potential to be produced locally using Indonesian resources, such as Ilmenite and silica sand, TiSi2 can promote self-sufficiency of the national strategic industry, including in the defence and energy sectors.